ANALISA KARAKTERISTIK BIODIESEL HASIL TRANSESTERIFIKASI MINYAK JELANTAH MENGGUNAKAN KATALIS KOH - Selvia Sarungu; Lukman Lukman; Sofia Lanrianna Putri Paelongan (Sekolah Tinggi Teknologi MIGAS, 2020)
The increasing demand for fossil fuels is resulting in the increase of the price and even some serious environmental problems. Researchers continue to develop research to find solutions to these problems. Renewable energy is needed to become an alternative fuel. Used cooking oil derived from vegetable oils and animal fats are considered feasible as the alternative fuels to replace petroleum because of their renewable nature. Used cooking oil after being reacted with methanol and a catalyst can be synthesized into biodiesel because it contains triglycerides. This research was conducted to obtain the characteristics of biodiesel yields that meet SNI quality standards. In the transesterification process, methanol and KOH are reacted with used cooking oil in a ratio of 1:2, 1:3 and 1:4. The transesterification process was carried out in a three necks flask and refluxed at an operating temperature of 60℃ for 60 minutes and deposited for 24 hours. Then it was washed until the biodiesel pH was neutral and was heated until the water content disappeared. After obtaining the biodiesel yield from the transesterification of used cooking oil, the analysis of characteristic was carried out to assess whether the produced biodiesel had met the SNI standards or not. The characteristics that were obtained from the biodiesel indicated that the density, saponification rate, free fatty acids and water content had met the biodiesel quality standards of SNI 7182:2006. Meanwhile, the acid numbers and viscosity did not meet the biodiesel quality standards of SNI 7182:2006.